La comunicación corporativa de la Federación Deportiva de Los Ríos al 2023 - Ramirez Valdiviezo, Mayerli Nikole (2023)
Corporate communication has marked a crucial point in the world of administration for business development or any other institution that wants to relate to as many people as possible, such is the case of the Los Ríos Sports Federation, which has a good management of information externally, communicating with its target audience through the social network Facebook, where it is very popular, it also has a website, however it would not hurt if new ways and strategies could be implemented to position the image of a sports entity. It has been noted that, within its internal management, it is deficient in the communication area, since it has a person who does the work of publishing, planning and managing the content to disseminate the activities carried out by the institution, therefore it is essential that increase staff, which would generate more reach and better organization in your communication processes. Improving the corporate communication plan will help to have more presence at the provincial and national level.